Load-bearing furniture modules for fast deployable and reusable systems - Riggio, Mariapaola; Dalle Vedove, Alberto; Piazza, Maurizio (Frontiers in Built Environment, 2024)
The urgent need to reduce carbon emissions in the construction sector has driven the exploration of circular economy practices in the built environment. Nevertheless, the implementation of circular economy principles in projects remains limited. This research contributes to bridging this gap by introducing a project proposal that establishes a typology of modular systems designed for easy assembly, disassembly, and reuse. Specifically, the proposal focuses on load-bearing wood furniture modules (FMs) as an intermediate solution between planar and volumetric modules. These FMs expand the structural wall's volume, facilitating the integration of services, storage, and appliances. This addresses scenarios where swift building deployment is required. The proposed modular dimension enhances transportation efficiency compared to volumetric solutions and simplifies construction by eliminating the need for temporary stabilization, as seen in planar systems. Standardization and 'separability' of each component within the FM allows for easy integration and maintenance. Special attention is paid to the timber connection systems within and between FMs facilitating easy assembly, and disassembly for future reuse. The adaptability of the FM concept is demonstrated through versatile compositions and layouts, facilitating space reconfiguration. While the technical feasibility of the FM-based system is demonstrated, further research is needed to address regional and cultural variations and customize the system to different contexts. The study emphasizes the potential of FMs as a solution for buildings aligned with circular economy principles and highlights the importance of continued research and development in this field.